x+(y+z)=(x+y)+z by taking x=-3/4,y=4/-7and z=-5/-4 Question x+(y+z)=(x+y)+z by taking x=-3/4,y=4/-7and z=-5/-4 in progress 0 Math Valentina 3 weeks 2021-10-01T20:25:25+00:00 2021-10-01T20:25:25+00:00 1 Answer 0 views 0

## Answers ( )

Answer:Verify x+(y+z)=(x+y)+z for the following values of x,y,z (i)x=3/4,y=5/6,z=-7/8(ii)x=2/3,y=-5/6,z=-7/9(iii)x=3/5,y=-6/9,z=2/10(iv)x=-3/5,y=-7/10,z=-8/15

To Verify x+(y+z)=(x+y)+z

(i)x=3/4,y=5/6,z=-7/8

LHS = 3/4 + (5/6 + (-7/8)) = (3/4) + (5/6 -7/8) = (3/4) + ((20 – 21)/24) = 3/4 – 1/24

= (18 – 1)/24 = 17/24

RHS = (3/4 + 5/6) + (-7/8) = (9 + 10)/12 – 7/8 = 19/12 – 7/8 = (38 – 21)/24 = 17/24

LHS = RHS = 17/24

(ii)x=2/3,y=-5/6,z=-7/9

LHS = 2/3 + (-5/6 + (-7/9) = 2/3 + ( -5/6 – 7/9) = 2/3 + (-29/18) = 2/3 – 29/18

= 12/18 – 29/18 = -17/18

RHS = (2/3 + (-5/6) ) + (-7/9) = (2/3 – 5/6) – 7/9 = (-1/6) – 7/9 = -1/6 – 7/9 = -3/18 – 14/18 = -17/18

LHS = RHS

Step-by-step explanation:I hope it helps you

mark me BRANLIST please